Path Analysis of Consumer Loyalty Factors to Viar Products - Rachmawati, R; Mulyani Azis, Y; Sutaryana, I (KnE Social Sciences, 2018)
This study aims to know (1) how loyal consumers are to Viar products, (2) what are the factors of consumer loyalty to Viar products, and (3) which factors have the most dominant loyalty to the purchase of Viar motor. The object of this research is the consumer dealer ViarArtomoro Bandung; using 33 people in the study sample, the method used is descriptive and uses the verification method where the researcher conducted direct observation through interviews and questionnaires to find out company activities and customer responses toward the ViarArtomoro dealer Bandung. The result of research shows that (1) overall, consumer loyalty to Viar products is still classified as normal, and it can be seen from the quality of the product, which is still considered less than good by the consumer as well as the service and promotion that is still considered good enough, while the price needs to be maintained; (2) consumer loyalty factors that significantly affect the purchase of Viar product are price, product quality, and promotion factors, while the service factor does not have any significant impact; (3) loyalty factors that give the most dominant contribution to purchasing Viar Motor is predominantly the price factor with contribution of 33.1%, followed by promotion factor at 26.5% and product quality factor at 19.1%. Keywords: loyalty factor, path analysis, Viar product